2011
DOI: 10.1093/wber/lhr013
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and the Brain Drain Revisited: The Microdata Show That More Educated Migrants Remit More

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(41 citation statements)
references
References 7 publications
0
39
1
1
Order By: Relevance
“…The evidence is still unclear on the relative propensity of high-skilled and low-skilled migrants to remit. In 14 household surveys on immigrants in 11 destination countries, the relationship between education and the likelihood of remitting is mixed, but the relationship between education and the amount remitted is strong and positive [9].…”
Section: Remittancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence is still unclear on the relative propensity of high-skilled and low-skilled migrants to remit. In 14 household surveys on immigrants in 11 destination countries, the relationship between education and the likelihood of remitting is mixed, but the relationship between education and the amount remitted is strong and positive [9].…”
Section: Remittancesmentioning
confidence: 99%
“…In the absence of surveys that match sending and receiving households, it remains difficult to quantify the effect of high-skilled migrant remittances on investment, poverty, or inequality in the home country. The economic consequences of remittances likely vary across home countries [9].…”
Section: Remittancesmentioning
confidence: 99%
“…Skilled migration has a number of important benefits: it generates remittances (Bollard et al, 2009), establishes social networks (Meyer, 2001) and diffuses knowledge (Le, 2008). Perhaps the most important positive effect, however, is incentivising education.…”
Section: The Empirical Debatementioning
confidence: 99%
“…According to a study by Bollard et al (2011), it is the levels of education among the emigrants that determines the quantity of remittances send back to the home country. Their study found out that highly educated emigrants are likely to remit more as they are more likely to be earning higher as compared to less educated emigrants, thereby supporting the education-led remittances hypothesis.…”
Section: Review Of Related Literaturementioning
confidence: 99%